Unravelling the novel mode of action of the spinosyn insecticides: A 25 year review - Trent Perry; Frank J. Wessels; Samantha Griffin; Chaoxian Geng; Natalie C. Giampietro; David G.J. Mann; Thomas C. Sparks (Pesticide Biochemistry and Physiology, 2025)

Characterising the innate immune response in breech strike resistant and non-selected sheep to the sheep blowfly (Lucilia cuprina) - Sugandhika G. Welikadage; Habtamu B. Derseh; Trent Perry; Clare A. Anstead; Jean-Pierre Y. Scheerlinck; Vern M. Bowles (Veterinary Immunology and Immunopathology, 2025)

Characterization of Caenorhabditis elegans transient receptor potential vanilloid (TRPV) channels and their interactions with insecticidal compounds - Samantha Griffin; Amanda Garbers; Lauren Banina; Trent Perry; Gerald Watson (Pesticide Biochemistry and Physiology, 2025)

Spinosyn resistance and cross-resistance – A 25 year review and analysis - Thomas C. Sparks; Frank J. Wessels; Trent Perry; Michael J. Price; Melissa W. Siebert; David G.J. Mann (Pesticide Biochemistry and Physiology, 2025)

A Case Study of Large Floodplain River Restoration: Two Decades of Monitoring the Merwin Preserve and Lessons Learned through Water Level Fluctuations and Uncontrolled Reconnection to a Large River - Levi E. Solomon; Andrew F. Casper; Kristopher A. Maxson; James T. Lamer; Trent W. Ford; K. Douglass Blodgett; Tharran Hobson; Denim Perry; Nathan T. Grider; Rob B. Hilsabeck; Thad R. Cook; Kevin S. Irons; et al. (Wetlands, 2022)

Functional characterization and fitness cost of spinosad-resistant alleles in Ceratitis capitata - Ana Guillem-Amat; Enric Ureña; Elena López-Errasquín; Vicente Navarro-Llopis; Philip Batterham; Lucas Sánchez; Trent Perry; Pedro Hernández-Crespo; Félix Ortego (Journal of Pest Science, 2020)
The sustainability of control programs for the Mediterranean fruit fly, Ceratitis capitata, for citrus crops in Spain has been threatened by the development of resistance to malathion and lambda-cyhalothrin in recent years. Spinosad is widely used without apparent loss of efficacy. However, a highly resistant strain, JW-100s, has been obtained after laboratory selection. Spinosad resistance in JW-100s has been associated with different mutant alleles of the α6 subunit of the nicotinic acetylcholine receptor ( Ccα6 ) including an isoform-specific truncation allele, Ccα6 3aQ68* . Using the GAL4 > UAS system in Drosophila melanogaster to demonstrate expression of this truncated α6 subunit, in a dα6 loss-of-function genetic background, does not rescue susceptibility to spinosad, while the expression of Ccα6 wild-type isoforms does. We have also generated C. capitata isolines from JW-100s homozygous for: (1) the Ccα6 3aQ68*Δ3b - 4 allele, which contains the mutation 3aQ68*, and (2) the Ccα6 3aQ68* – K352* allele, which contains the mutations 3aQ68* and K352*. Neither of these produce complete Ccα6 transcripts. The frequency of resistant alleles declined when in competition with individuals carrying the wild-type allele. Through extensive testing of both biological and behavioral fitness traits, we identified a reduced ability of Ccα6 3aQ68*Δ3b - 4 males to detect the parapheromone and to mate with females carrying the Ccα6 3aQ68* – K352* allele in competition experiments. Thus, not only the potential for spontaneous resistant mutations to arise in Ccα6 but also their fitness costs must be considered when planning resistance management strategies for C. capitata .

The Genetic Basis of Resistance to Diazinon in Natural Populations of Drosophila melanogaster - Fiona M. Pyke; Michael R. Bogwitz; Trent Perry; Adrian Monk; Philip Batterham; John A. McKenzie (Genetica, 2004)